Causal analysis of the gut microbiota in differentiated thyroid carcinoma: a two-sample Mendelian randomization study - Quan, Zheng; Zhang, Xiaoyu; Wang, Shilong; Meng, Yong (Frontiers in Genetics, 2023)
Objective: Numerous studies have highlighted an association between the gut microbiota(GM) and thyroid tumors. Employing Mendelian randomization methodology, we seek to elucidate the causal link between the gut microbiota and thyroid neoplasms.Methods: We procured data from the Mibiogen database encompassing 211 distinct gut microbiota taxa, alongside extensive genome-wide association studies (GWAS) summary data for differentiated thyroid carcinoma (DTC). Our principal analytical approach involved the application of the Inverse-Variance Weighted method (IVW) within the framework of Mendelian randomization. Simultaneously, we conducted sensitivity analyses to assess result heterogeneity, horizontal pleiotropy, and outcome stability.Results: IVW analysis revealed a dual role of the GM in thyroid carcinoma. The phylum Actinobacteria (OR, 0.249 [95% CI, 0.121 -0.515]; P < 0.001) was associated with a decreased risk of DTC. Conversely, the genus Ruminiclostridium9 (OR, 11.276 [95% CI,; P < 0.001), class Mollicutes (OR, 5.902 [95% CI,; P = 0.004), genus RuminococcaceaeUCG004 (OR, 3.831 [95% CI,]; P = 0.005), genus Paraprevotella (OR, 3.536 [95% CI,]; P = 0.011), and phylum Tenericutes (OR, 5.902 [95% CI,]; P = 0.004) were associated with an increased risk of DTC.Conclusions: Our findings underscore that the presence of genus Ruminiclostridium9, class Mollicutes, genus RuminococcaceaeUCG004, genus Paraprevotella, and phylum Tenericutes is associated with an elevated risk of DTC, whereas the presence of the phylum Actinobacteria is linked 2 to a decreased risk. These discoveries enhance our comprehension of the relationship between the GM and DTC.